#### Answer

{7}

#### Work Step by Step

11x - (6x - 5) = 40
Step 1 : Drop parentheses and change the sign of each term in parentheses: - (6x - 5) = -6x + 5
11x - 6x +5 =40
Step 2: Combine like terms 11x - 6x = (11-6)x =5x
5x + 5 = 40
Step 3: subtract 5 from both the sides
5x+ 5 - 5 =40 -5
Step 4: Simplify
5x = 35
Step 5: Divide both the sides by 5
$\frac{5x}{5}$ = $\frac{35}{5}$
Step 6: Simplify
x = 7
Now we check the proposed solution,7 , by replacing x with 7 in the original equation.
Step 1: the original equation 11x - (6x -5) = 40
Step2: Substitute 7 for x
11.7 - (6.7 - 5) =40
Step 3: Multiply 11.7 = 77 and 6.7 = 42
77 - (42 - 5) = 40
Step 4: Solve parenthesis 42 - 5 = 37
77 - 37 = 40
Step 5: Subtract
40 = 40
Since the check results in true statement, we conclude that the solution set of the given equation is {7}